Gaya Bahasa dalam Novel Seporsi Mie Ayam Sebelum Mati Karya Brian Khrisna - Syamsinar; Idawati; Sakaria (STKIP Subang, 2026)
Language Style in the Novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. This study aims to describe the language styles found in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. This study uses a qualitative descriptive approach with a library study method. The research data are in the form of narrative excerpts and dialogues containing elements of language styles in the novel. The data source for this research is the text of the novel Seporsi Mie Ayam Sebelum Mati. Data collection was carried out through reading and note-taking techniques with the stages of identification and classification. The research instrument was the researcher herself who was assisted by a data recording sheet based on the language style categories according to Keraf. The data analysis technique used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study show that this novel contains various language styles, namely language styles based on sentence structure such as climax, repetition, antithesis, and rhetoric, as well as language styles based on meaning such as metaphor, simile, personification, hyperbole, litotes, irony, and sarcasm. The use of these language styles serves to strengthen expression, build an emotional atmosphere, and enrich the beauty of the language in the novel.